Perinatal and maternal morbidity and mortality among term singletons following midcavity operative vaginal delivery versus caesarean delivery - Muraca, GM (BJOG, 2017)
OBJECTIVE: To quantify severe perinatal and maternal morbidity/mortality associated with midcavity operative vaginal delivery compared with caesarean delivery. DESIGN: Population‐based, retrospective cohort study. SETTING: British Columbia, Canada. POPULATION: Term, singleton deliveries (2004–2014) by attempted midcavity operative vaginal delivery or caesarean delivery in the second stage of labour, stratified by indication for operative delivery (n = 10 901 deliveries; 5057 indicated for dystocia, 5844 for fetal distress). METHODS: Multinomial propensity scores and mulitvariable log‐binomial regression models were used to estimate adjusted rate ratios (ARR) and 95% confidence intervals (95% CI). MAIN OUTCOME MEASURES: Composite severe perinatal morbidity/mortality (e.g. convulsions, severe birth trauma and perinatal death) and severe maternal morbidity (e.g. severe postpartum haemorrhage, shock, sepsis and cardiac complications). RESULTS: Among deliveries with dystocia, attempted midcavity operative vaginal delivery was associated with higher rates of severe perinatal morbidity/mortality compared with caesarean delivery (forceps ARR 2.11, 95% CI 1.46–3.07; vacuum ARR 2.71, 95% CI 1.49–3.15; sequential ARR 4.68, 95% CI 3.33–6.58). Rates of severe maternal morbidity/mortality were also higher following midcavity operative vaginal delivery (forceps ARR 1.57, 95% CI 1.05–2.36; vacuum ARR 2.29, 95% CI 1.57–3.36). Among deliveries with fetal distress, there were significant increases in severe perinatal morbidity/mortality following attempted midcavity vacuum (ARR 1.28, 95% CI 1.04–1.61) and in severe maternal morbidity following attempted midcavity forceps delivery (ARR 2.34, 95% CI 1.54–3.56). CONCLUSION: Attempted midcavity operative vaginal delivery is associated with higher rates of severe perinatal morbidity/mortality and severe maternal morbidity, though these effects differ by indication and instrument. TWEETABLE ABSTRACT: Perinatal and maternal morbidity is increased following midcavity operative vaginal delivery.